PEMBINAAN PENYELENGGARA ADMINISTRASI PEMERINTAH DESA OLEH KECAMATAN DIKECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Fanny Rahma Sari; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The research discusses abaout Coaching of village government administration by the distrik iin Gunung Toar districk Kuantan Singingi regency. The purpose of this research (1) to find out the implementation of development of village government administration in Gunung Toar regency, (2) to fine factors that become obstacles in the implementation of coacing village government administration. The research method use is qualitative. From the result of the study, not all village administration ar well structured and complete. And that should be done of Gunung Toar regency is improve human resources, coordination and communication with village officials and provide motivation that can spur enthusiasm in discipiling village administration so that goals can be maximally achieved. Keywords: Management, Choacin, government administration